2019
DOI: 10.1016/j.taap.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic secoisolariciresinol diglucoside (LGM2605) inhibits Libby amphibole fiber-induced acute inflammation in mice

Abstract: Background: Exposure to the Libby Amphibole (LA) asbestos-like fibers found in Libby, Montana, is associated with inflammatory responses in mice and humans, and an increased risk of developing mesothelioma, asbestosis, pleural disease, and systemic autoimmune disease. Flaxseed-derived secoisolariciresinol diglucoside (SDG) has anti-inflammatory, anti-fibrotic, and antioxidant properties. We have previously identified potent protective properties of SDG against crocidolite asbestos exposure modeled in mice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Moreover, NO metabolites can interact with endothelial damage, inflammation, and vascular disease [27,28]. We also found that SDG inhibits the expression of proinflammatory cytokines, which is consistent with our previous and other findings [11,29]. Studies have shown that immune inflammation is a key factor in the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, NO metabolites can interact with endothelial damage, inflammation, and vascular disease [27,28]. We also found that SDG inhibits the expression of proinflammatory cytokines, which is consistent with our previous and other findings [11,29]. Studies have shown that immune inflammation is a key factor in the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we utilized the synthetic flaxseed lignan LGM2605 as a form of dietary intervention in mice. Previous studies have shown that LGM2605 acts as an antioxidant and free radical scavenger (Pietrofesa, Velalopoulou, Arguiri, et al, 2016), reducing inflammation associated with radiation and asbestos exposure (Christofidou‐Solomidou et al, 2019; Mishra et al, 2020; Velalopoulou et al, 2015); however, its effects on gut microbiota have not previously been evaluated. We therefore sought to determine how a 10‐day period of oral LGM2605 administration affects the gut microbial composition of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the synthetic flaxseed lignan LGM2605 has been evaluated as a therapeutic alternative to naturally occurring SDG, as it has significantly greater bioavailability compared to whole flaxseed and can be readily produced in a laboratory setting (Mishra et al, 2013). Previous studies have demonstrated the usefulness of LGM2605 in controlling inflammation and oxidative stress responses in models of radiation and asbestos exposure, likely resulting from the ability of LGM2605 to scavenge radical species and reduce inflammatory cytokine production (Christofidou‐Solomidou et al, 2019; Mishra et al, 2020; Pietrofesa et al, 2014; Pietrofesa, Velalopoulou, Arguiri, et al, 2016; Velalopoulou et al, 2015). The protective effects of LGM2605 may be especially important in lung and breast cancer radiation therapies to reduce damage to bystander organs (Velalopoulou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SDG is a potent antioxidant with anti-inflammatory and antifibrotic properties; the beneficial effects of SDG have been documented in treating hypercholesterolemia, diabetes, postmenopausal symptoms, cardiovascular disease, metabolic syndrome, bone disease, ischemia-reperfusion injury, radiation-induced pneumonopathy and hyperoxia [ 69 ], and references therein. Chemically synthesized SDG, LGM2605 is effective in several preclinical models of disease in which oxidative stress and inflammation play a prominent role in pathogenesis [ 35 , 39 , 40 , 41 ]. Herein, we show for the first time that LGM2605 protects the RPE against lipid overload and oxidative stress mediated cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…SDG has potent free radical scavenging and antioxidant properties and confirms its DNA radioprotective properties in cell-free systems [ 36 ] as well as in cells [ 37 , 38 ]. In preclinical models in mice [ 35 , 39 , 40 , 41 ], non-human primates [ 42 ] and in an ex vivo lung organ culture model of proton-irradiated human lung, LGM2605 [ 43 ] has been shown to be highly efficacious. LGM2605 exhibits free radical scavenging, antioxidant and anti-inflammatory properties in diverse inflammatory cells (Rom, 2018 #43; Kokkinaki, 2019 #38; Christofidou-Solomidou, 2012 #55; Mishra, 2013 #48; Velalopoulou, 2017 #47; Velalopoulou, 2015 #42; Pietrofesa, 2016 #62; Pietrofesa, 2017 #54).…”
Section: Introductionmentioning
confidence: 99%